Repository and its place at the University of Pardubice - Vyčítalová, Lucie (My University, 2014)
The main impulsion to consider the repository at the university was the amendment of the Higher Education Act. According to this amendment, the university is obliged to make accessible the submitted and accepted theses and dissertations. After the analysis of the current system, we have made a decision to create an institutional repository and the DSpace installation was launched in 2007. The structure of communities and collections copies the university environment (faculties, departments) precisely. Nowadays the theses metadata and full-text are regularly submitted to the repository from the university information system. The repository is also open to submit university research outputs (books, articles, conference proceedings). Some titles are submitted regularly by the cooperation with the university publishing center. Articles in accordance with the open access rules are submitted irregularly on the cooperation with the researchers. Each record is equipped by the value added information and statistics. By setting up the OAI-PMH, the repository became an open archive and its content can be searchable via the world registers and systems. In 2012 the repository was adapted to the OpenAIRE project and also added to the university discovery system Primo. The poster will also introduce the current works on the repository connection with the university system for managing bibliographic data of research outputs. The plan is regular metadata imports from the Web of Science and Scopus to help and make easier submitting the metadata to the system for our researchers.
Keywords: repository; Univerzita Pardubice; scholarly communication